Bioaktivitas Usnea barbata (L.) F.H. Wigg sebagai Insektisida Nabati Coptotermes curvignathus (Holmgren) - Helmiyetti Helmiyetti; Rochmah Supriati; Risky Hadi Wibowo; Dian Fita Lestari; Leni Maryana (Jurnal Ilmu Pertanian Indonesia, 2023)
The subterranean termite Coptotermes curvignathus is a type of insect that damages wood until it is porous and destroyed. Until now, termites are chemically controlled but negatively impact the environment, so bioinsecticides such as from Usnea barbata lichen are needed. This study aims to determine the bioactivity of U extract. Barbata as a bioinsecticide for subterranean termites C. curvignathus. The experiment used Completely Randomizd Design with 7 treatments (concentrations of 0%, 5%, 10%, 15%, 20%, 25%, and Termicon) and 3 replicates. The extract was prepared from 300 g of U barbata powder, macerated in 7 days in 96% ethanol in a ratio of 1:10 (300 g/3 L). Mortality and feed weight loss were observed for 7 days. The extracts contained alkaloids, flavonoids, terpenoids, steroids, saponins, and tannins. The phytochemicals were analyzed descriptively, and a lethal concentration value of 50% (LC50) was determined by probit analysis. Data on termite mortality percentage and feed loss percentage were analyzed using ANOVA at a 5% confidence level. If the Fcalct > Ftable, Duncan's further test was carried out. The results showed that the extract contained alkaloids, steroids, tannins, and saponins. The mortality of subterranean termites was indicated by an LC value of 50-72 hours of 19.32%. Statistically, U. barbata extract affected mortality but did not differ significantly in the feed weight loss of C. curvignathus subterranean termites. Keywords: bioactivity, Coptotermes curvignathus, insecticide, Usnea barbata